Potensial Terapi Antikanker Melalui Senyawa Bioaktif dari Nutrasetikal - Winda Puspita sari (Jurnal Ilmu Medis Indonesia, 2022)
Purpose: This review aims to examine the current knowledge regarding to the molecular mechanisms by several nutraceuticals, such as retinoids, resveratrol, epigallocatechin 3 gallate, and omega-3 PUFAs to against cancer. Bioactive compounds with high contents in nutraceuticals are considered as complementary components in foods, dietary supplements, and medicines. These compounds can also inhibit carcinogenesis, protect body cells from inflammatory and oxidative processes, and induce anti-proliferative effects in various types of neoplasia. Research Methodology: The method used is a literature review. The literature search was conducted through Pubmed using keywords in the 2012-2021 timeframe. Result: The results obtained are that bioactive compounds from nutraceuticals, such as RSV, retinoids, EGCG, and omega-3 PUFAs, have the ability to influence the growth and development of cancer cells, therefore, nutraceuticals can work as innovative anticancer agents. Limitations: By this method, a thorough literature search may miss important studies that influence conclusions. Contribution: This research can be applied by all of cancer patients because nutraceutical ingredients are easily available throughout the world, including Indonesia.